2017
DOI: 10.3747/co.24.3454
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physician Services during the Survivorship Phase: A Multi-Province Study of Women Diagnosed with Breast Cancer

Abstract: Introduction Oncologists have traditionally been responsible for providing routine follow-up care for cancer survivors; in recent years, however, primary care providers (pcps) are taking a greater role in care during the follow-up period. In the present study, we used a longitudinal multi-province retrospective cohort study to examine how primary care and specialist care intersect in the delivery of breast cancer follow-up care.Methods Various databases (registry, clinical, and administrative) were linked in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Second, our study was conducted in a single Canadian province, and it is unclear whether and how patterns of follow-up care in other jurisdictions would be similar. A recent multi-province study examining physician visits in the follow-up care period found similar overall patterns of care, and yet breast cancer survivors in Nova Scotia had fewer oncologist visits during the follow-up period than did survivors in British Columbia, Manitoba, or Ontario 18 . Despite that limitation, our findings point to the need for further study in various Canadian jurisdictions to understand whether their patterns of follow-up care are similar and how those patterns are changing over time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, our study was conducted in a single Canadian province, and it is unclear whether and how patterns of follow-up care in other jurisdictions would be similar. A recent multi-province study examining physician visits in the follow-up care period found similar overall patterns of care, and yet breast cancer survivors in Nova Scotia had fewer oncologist visits during the follow-up period than did survivors in British Columbia, Manitoba, or Ontario 18 . Despite that limitation, our findings point to the need for further study in various Canadian jurisdictions to understand whether their patterns of follow-up care are similar and how those patterns are changing over time.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Grunfeld and colleagues 13 found that most breast cancer survivors diagnosed in Ontario between 1998 and 1999 received follow-up care from oncologists, either solely or in combination with care from pcps. A more recent investigation examining physician visits in four Canadian provinces (British Columbia, Manitoba, Ontario, Nova Scotia) for breast cancer survivors diagnosed between 2007 and 2010 or 2011, depending on province 18 , revealed that 65% -93% of women had visits to both pcps and oncology specialists during the follow-up period (1-5 years after diagnosis). Although those findings are not directly comparable with ours, the lower proportion of breast cancer survivors receiving specialist follow-up in our study might relate to how researchers compute follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…But the barriers and challenges that were also mentioned limit the ability of fps to fulfil that role, echoing those that we have lamented for almost 30 years 3 . ■ The papers by Kendell and colleagues 10 and Bastedo and colleagues 11 use population-based quantitative methods to describe, respectively, the utilization of physician services during survivorship and during active chemotherapy. O'Brien and colleagues 12 ask an innovative question about the potential role of fps in supporting patient decision-making with respect to personalized medicine.…”
Section: Examining the Two Solitudes In Canadamentioning
confidence: 99%
“…Ongoing email communications and a number of face-to-face meetings attended by key members complete our communication strategy. Through this communication strategy we refined and operationalized the research objectives, identified and processed data elements using standardized definitions, and developed ten study objectives and analysis plans for publication (22)(23)(24).…”
Section: Data Management Approachmentioning
confidence: 99%